2009
DOI: 10.1016/j.ejvs.2008.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Carotid Ultrasound for the Detection of Unstable Plaques with Neoangiogenesis: A Pilot Study

Abstract: Contrast carotid ultrasonography may allow the identification of microvessels with neoangiogenesis at the base of carotid plaques, and differentiate symptomatic from asymptomatic plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 26 publications
5
76
2
3
Order By: Relevance
“…Systematic histopathological validation revealed a direct positive correlation between contrast enhancement using this semi-quantitative grading scale and histology [44,45]. Furthermore, wholly consistent with the concept that more vulner- able plaque contains a higher degree of neovascularization, recent retrospective studies revealed the association between plaque enhancement on contrast-enhanced ultrasound imaging and clinical symptoms including cerebrovascular events in patients with carotid atherosclerosis [19,46,47]. Therefore, contrast-enhanced ultrasound examination of the carotid artery may provide a novel, noninvasive clinical tool to identify and quantify the presence and the extent of arterial plaque neovascularization in patients at risk for developing symptomatic atherosclerosis, thus permitting more reliable assessment of cardiovascular risk.…”
Section: Plaque Neovascularization On Contrast-enhanced Ultrasound Imsupporting
confidence: 65%
See 2 more Smart Citations
“…Systematic histopathological validation revealed a direct positive correlation between contrast enhancement using this semi-quantitative grading scale and histology [44,45]. Furthermore, wholly consistent with the concept that more vulner- able plaque contains a higher degree of neovascularization, recent retrospective studies revealed the association between plaque enhancement on contrast-enhanced ultrasound imaging and clinical symptoms including cerebrovascular events in patients with carotid atherosclerosis [19,46,47]. Therefore, contrast-enhanced ultrasound examination of the carotid artery may provide a novel, noninvasive clinical tool to identify and quantify the presence and the extent of arterial plaque neovascularization in patients at risk for developing symptomatic atherosclerosis, thus permitting more reliable assessment of cardiovascular risk.…”
Section: Plaque Neovascularization On Contrast-enhanced Ultrasound Imsupporting
confidence: 65%
“…2, 3). Recent studies have shown that the grayscale values of symptomatic versus asymptomatic plaques differ significantly [19]. Visual scores, however, have the disadvantage of relatively high subjectivity, which is illustrated by a rather poor interrater and intrarater correlation [20].…”
Section: B-mode Imaging For Displaying Plaque Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound contrast agents have been administrated in millions of patients and are safe and side effects are extremely rare [11] . The presence of ultrasound contrast agents in carotid artery plaque represents the presence of the vasa vasorum in carotid artery plaque (Figures 1 and 2) because the ultrasound contrast agents (SonoVue) are strict intravascular tracers, and the appearance of contrast enhancement of CEUS was shown to correlate with the presence and degree of the vasa vasorum in carotid artery plaque which were assessed by histology [12,13] .…”
Section: Editorialmentioning
confidence: 99%
“…There are too many criterions about assessment of the vasa vasorum in carotid artery plaque with CEUS at the present [4][5][6][7][8][9]12,13] , which includes quantitative criterion, semi-quantitative criterion and qualltative criterion [4][5][6][7][8][9] , therefore, the criterion of assessment of the vasa vasorum in carotid artery plaque with CEUS is inconsistent among all kinds of clinical studies [4][5][6][7][8][9]12,13] . Thus, the clinical value of the vasa vasorum in carotid artery plaque with CEUS yet remain sure accurately, therefore, the criterion about assessment of the vasa vasorum in carotid artery plaque with CEUS should be assessed in the future studies.…”
Section: Criterion Of Assessmentmentioning
confidence: 99%